2020
DOI: 10.3390/s20143995
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stages Classification of Potato Crop Based on Analysis of Spectral Response and Variables Optimization

Abstract: Potato is the world’s fourth-largest food crop, following rice, wheat, and maize. Unlike other crops, it is a typical root crop with a special growth cycle pattern and underground tubers, which makes it harder to track the progress of potatoes and to provide automated crop management. The classification of growth stages has great significance for right time management in the potato field. This paper aims to study how to classify the growth stage of potato crops accurately on the basis of spectroscopy technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 59 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…To study the stripping response law of Pb 2+ in the existence of different Cu 2+ concentrations, the concentration of Pb 2+ was set with 10 gradients, which were 1,5,10,15,20,25,30,35,40, and 45 µg/L. The Cu 2+ concentration was set with seven gradients, which were 0, 1, 5, 10, 15, 20, and 25 µg/L, because the peak current of Pb 2+ was extremely small and kept decreasing when the Cu 2+ concentration exceeded 25 µg/L.…”
Section: Collection Of Pb 2+ and Cu 2+ Swasv Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the stripping response law of Pb 2+ in the existence of different Cu 2+ concentrations, the concentration of Pb 2+ was set with 10 gradients, which were 1,5,10,15,20,25,30,35,40, and 45 µg/L. The Cu 2+ concentration was set with seven gradients, which were 0, 1, 5, 10, 15, 20, and 25 µg/L, because the peak current of Pb 2+ was extremely small and kept decreasing when the Cu 2+ concentration exceeded 25 µg/L.…”
Section: Collection Of Pb 2+ and Cu 2+ Swasv Signalsmentioning
confidence: 99%
“…The introduction of the kernel function achieves the purpose of increasing the dimension, and the added parameters are adjustable and optimizable to prevent overfitting questions. Many scholars have indicated that the radial basis function net is an efficient tool for the fitting of a nonlinear relationship [25,33]. Therefore, in this study, a radial basis function was selected as the SVR kernel function to discover and interpret the nonlinear relationship between the stripping peak currents of Pb 2+ and Cu 2+ and the Pb 2+ concentration.…”
Section: Svr Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of N nutrition in crops based on spectral data has made considerable progress [17]. The technique has been applied in several crops to rapidly obtain crop N nutrition status spectral indices derived from spectral [18][19][20]. Several researchers have developed crop N nutrition monitoring models based on spectral indices, and achieved high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Potato (Solanum tuberosum) is the world's fourth-largest food crop following rice, wheat, and maize [1,2]. Chlorophyll, as the essential photosynthetic pigment of potato leaves, reflects growth information about plant health [3] and photosynthetic rate [4], and its content is also significantly correlated with the concentration of nitrogen [5].…”
Section: Introductionmentioning
confidence: 99%